2011
DOI: 10.1016/j.aanat.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases as regulators of morphological neuroplasticity

Abstract: SummaryGTPases function as intracellular, bimolecular switches by adopting different conformational states in response to binding GDP or GTP. Their activation is mediated through cell-surface receptors. Rho GTPases act on several downstream effectors involved in cellular morphogenesis, cell polarity, migration and cell division. In neurons, Rho GTPases regulate various features of dendritic and axonal outgrowth during development and regeneration mainly through their effects on the cytoskeleton. This review su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 108 publications
0
65
0
Order By: Relevance
“…Our results suggest that autophagy regulates axon growth via upregulation of the RhoA-ROCK pathway in developing neurons. RhoA and its downstream effector, ROCK, are well-known negative regulators of the early stages of axon extension in cultured neurons (72)(73)(74). Indeed, forced expression of the wild-type or constitutive active form of RhoA in autophagy-deficient neurons rescued the axon elongation phenotype caused by autophagy reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that autophagy regulates axon growth via upregulation of the RhoA-ROCK pathway in developing neurons. RhoA and its downstream effector, ROCK, are well-known negative regulators of the early stages of axon extension in cultured neurons (72)(73)(74). Indeed, forced expression of the wild-type or constitutive active form of RhoA in autophagy-deficient neurons rescued the axon elongation phenotype caused by autophagy reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Cdc42 deregulation has been linked to various aspects of tumorigenesis, including transformation and metastasis (3,39). Additionally, neuronal development and maintenance relies heavily on appropriate Cdc42 activity (8). Given the urgent need to discover an effective tool for Cdc42 study, we undertook a similar strategy in the discovery of NSC23766 and identified potential Cdc42 inhibitors by screening more than 197,000 small molecules coupled with biochemical and cell-based verifications.…”
Section: Discussionmentioning
confidence: 99%
“…Cdc42 has been attributed to several aspects of cancer, including cellular transformation (10) and metastasis (11,12). As a key regulator of neurite morphogenesis, Cdc42 has also been shown to be crucial for normal brain development, as conditional Cdc42 KO mice do not survive birth and show gross brain abnormalities (8,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3B). NEP1-40, which acts as a selective, competitive and high affinity antagonist of NgR1 [38,39] was used to block NgR1 interaction with Nogo-p4. Results showed that while Nogo-p4 inhibited NGF-induced neurite growth by 52%, NEP1-40 significantly attenuated the inhibition by 37% (Fig.…”
Section: Figmentioning
confidence: 99%